Methods of study and the essence of methods of geometric transformations as methods of proving - Yarova, Oksana Anatoliivna; Skaskiv, Liliia Vasylivna; Martynenko, Valentyna Vitaliivna (Ljubljana, Slovenia, 2021)
The article considers the peculiarities of the method of applying the methods of geometric transformations for solving problems to prove in the school course of mathematics.

У статті розглядаються особливості методики застосування методів геометричних перетворень для розв’язування задач на доведення у шкільному курсі математики.
Keywords: method of geometric transformations; homothety; symmetry; problems on proof; метод геометричних перетворень; гомотетія; симетрія; задачі на доведення